ANALISIS PUTUSAN PENGADILAN TINGGI MEDAN NOMOR 66/PID.SUS/2018/PT.MDN TERKAIT TINDAK PIDANA PERPAJAKAN - Tjoe Kang Long; Tanudjaja Tanudjaja (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
If in the activities of a company there is a criminal element, then in this case there is a criminal act of taxation, even if it is committed by the company itself, and although it is subject to responsibility, there is no legal basis for the theory of piercing the veil of the corporation Justified. To other parties such as directors or shareholders. Provisions regarding beneficial rights have not been regulated in the Criminal Procedure Code and the Tax Procedure Law, but beneficial owners can be held accountable as parties who have the power to control the company, such as giving instructions to the company's directors. In Indonesia, beneficiary ownership rights include Financial Services Authority Regulation No.12/POJK. 01/2017 dated March 16, 2017 concerning the Implementation of Anti-Money Laundering and Anti-Terrorist Financing Programs in Financial Services; It is strictly regulated by several laws. Unfortunately, this provision does not apply in the Presidential Regulation of the Republic of Indonesia Number 13 of 2018 concerning the Application of the Principle of Recognizing Business Excellence in the Framework of Prevention and Eradication of Money Laundering and Terrorist Financing. Crime in the field of taxation. In the field of taxation, the regulation regarding beneficial owners is very limited and only applies to foreign taxpayers, so it still provides opportunities for beneficiaries in the sense of actual beneficial owners to commit tax crimes.